The Importance of Leadership in Enhancing Work Performance (Case: Education Bureau of Sidenreng Rappang Regency) - Nugrawan Saharuddin; Alamsyah Agit; Dian Novianti (Asian Journal of Management Analytics, 2023)
Leadership is one of the most important factors that could influence work performance. The leadership approach starts with the emotional aspect, which could effectively influence work performance in the short or long run. The purpose of this paper is to explore the importance of leadership in enhancing work performance. The paper consists of a quantitative study that looks at how leadership impacts work performance using numerical methodologies. The results of this paper show the positive and significant influence of leadership on work performance. This result reflected the real-life condition in which the quality of leadership affects work performance, since the main approach of leadership indirectly dives into the emotional aspect, which can spark motivation and satisfaction, which in turn lead to high work performance as the result of effort and hard work from the employee.